Pengembangan E-LKPD Berbantuan Android pada Mata Pelajaran IPA Kelas VIII di SMP - Asri Febriyanti; Zuliarni Zuliarni; Alwen Bentri; Novrianti Novrianti (Departement of Mathematics Education, 2023)
The background for the development of the Android-assisted E-LKPD was that the science practicum activities in the laboratory could not be carried out on time because they had to take turns with other classes, and the practicum tools were not qualified to support science learning. Teachers use teaching materials such as textbooks and LKS. Textbooks only contain text and pictures, cannot contain videos and animations that support it so that students do not understand the material and have difficulty relating learning to everyday life. In science learning itself, there are many discussions that require animation, if you are only guided by printed books, what is conveyed will not be realized. The purpose of this study was to produce valid and practical android-assisted E-LKPD in Class VIII science subjects in junior high schools. The type of development used is Research and Development (R&D). The development model used in this study uses the model proposed by Borg and Gall up to 5 stages of development. The data obtained will be analyzed using a Likert scale. The development of the Android-assisted E-LKPD was assessed by 2 media validators, namely lecturers from the Department of Curriculum and Educational Technology and material validators, namely Science Subject Teachers at SMPN 3 Pariaman. The practicality assessment was carried out by 15 class VIII students of SMPN 3 Pariaman. The product validity test results for the media aspect are categorized as